Assessment of Radio Frequency Compatibility for New Radio Navigation Satellite Service Signal Design in the L6-Band - Subin Lee; Kahee Han; Jong-Hoon Won (Remote Sensing, 2024)
The L- and S-bands are becoming increasingly congested with the modernization of radio navigation satellite service (RNSS) systems and the development of a new satellite navigation system. In order to solve the problem of frequency band congestion, compatibility performance assessment is essential when designing a new RNSS signal. This paper proposes a three-step compatibility assessment methodology for the design of new RNSS signals and evaluates the compatibility performance of L6-band signals based on the proposed methodology. The open signals of Galileo, the BeiDou Navigation Satellite System (BDS), and the Quasi-Zenith Satellite System (QZSS), as well as the three candidate signals of the new RNSS, are considered for the compatibility assessment. Based on the assessment results, this paper shows that the interference caused by the introduction of a new RNSS signal in the L6-band is tolerable.